Incomplete Penetrance and Variable Expressivity: From Clinical Studies to Population Cohorts - Kingdom, Rebecca; Wright, Caroline F. (Frontiers in Genetics, 2022)
The same genetic variant found in different individuals can cause a range of diverse phenotypes, from no discernible clinical phenotype to severe disease, even among related individuals. Such variants can be said to display incomplete penetrance, a binary phenomenon where the genotype either causes the expected clinical phenotype or it doesn’t, or they can be said to display variable expressivity, in which the same genotype can cause a wide range of clinical symptoms across a spectrum. Both incomplete penetrance and variable expressivity are thought to be caused by a range of factors, including common variants, variants in regulatory regions, epigenetics, environmental factors, and lifestyle. Many thousands of genetic variants have been identified as causal of monogenic disorders, mostly determined through small clinical studies, and thus the penetrance and expressivity of these variants may be overestimated when compared to their effect in the general population. With the wealth of population cohort data currently available, the penetrance and expressivity of such genetic variants can be investigated across a much wider contingent, potentially helping to reclassify variants that were previously thought to be completely penetrant. Research into the penetrance and expressivity of such genetic variants is important for clinical classification, both for determining causative mechanisms of disease in the affected, and for providing accurate risk information through genetic counselling. A genotype-based definition of the causes of rare disease incorporating information from population cohorts as well as clinical studies is critical for our understanding of incomplete penetrance and variable expressivity. This review examines our current knowledge of the penetrance and expressivity of genetic variants in rare disease and across populations, as well as looking into the potential causes of the variation seen, including genetic modifiers, mosaicism, and polygenic factors, among others. We also consider the challenges that come with investigating penetrance and expressivity.